2020
DOI: 10.1016/j.xcrm.2020.100146
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine Inhibits the Trained Innate Immune Response to Interferons

Abstract: Highlights d PBMCs of COVID-19 patients show increased responses to Toll-like receptor ligands d Trained immunity is modeled in vitro using Candida-trained PBMCs d Hydroxychloroquine inhibits changes in lipidome and histone modifications d Hydroxychloroquine dampens the trained response to interferons and viral stimuli

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 64 publications
0
25
0
Order By: Relevance
“…Chloroquine, an antimalarial drug, was proposed as therapeutic agent for COVID-19 because they were observed to inhibit SARS-CoV-2 viral replication in vitro in primate cells [ 5 ]; however, a later study found that chloroquine did not inhibit infection of human lung cells with SARS-CoV-2 [ 34 ]. HCQ, a less toxic derivative of chloroquine, inhibits trained immunity in vitro in peripheral blood mononuclear cells, which may not be beneficial for the antiviral innate immune response to SARS-CoV-2 infection in patients [ 35 ]. Chloroquine also has been investigated in vitro as potential treatment for other viruses such as human immunodeficiency virus [ 36 ], human coronavirus OC43, enterovirus EV-A71, Zika virus, influenza A H5N1, hepatitis C virus and chikungunya virus [ 37 ]; however, these studies did not show beneficial effects.…”
Section: Discussionmentioning
confidence: 99%
“…Chloroquine, an antimalarial drug, was proposed as therapeutic agent for COVID-19 because they were observed to inhibit SARS-CoV-2 viral replication in vitro in primate cells [ 5 ]; however, a later study found that chloroquine did not inhibit infection of human lung cells with SARS-CoV-2 [ 34 ]. HCQ, a less toxic derivative of chloroquine, inhibits trained immunity in vitro in peripheral blood mononuclear cells, which may not be beneficial for the antiviral innate immune response to SARS-CoV-2 infection in patients [ 35 ]. Chloroquine also has been investigated in vitro as potential treatment for other viruses such as human immunodeficiency virus [ 36 ], human coronavirus OC43, enterovirus EV-A71, Zika virus, influenza A H5N1, hepatitis C virus and chikungunya virus [ 37 ]; however, these studies did not show beneficial effects.…”
Section: Discussionmentioning
confidence: 99%
“…The monocyte COVID-19 RNA-Seq data, published under the accession GSE159678 (Rother et al, 2020), was downloaded from SRA and gene expression was quantified using Salmon's selective alignment approach (Srivastava et al, 2020). The RNA-Seq processing pipeline was implemented using pyrpipe (Singh et al, 2021) (https://github.com/urmi-21/pyrpipe/tree/master/case_studies/ Covid_RNA-Seq).…”
Section: Star+methodsmentioning
confidence: 99%
“…We used this pipeline to quantify RNA-Seq data from a COVID-19 study of circulating monocytes ( 28 ), and provide output that can be directly analyzed by biologists, using the versatile Java software for exploratory analysis of large datasets, MetaOmGraph (MOG).…”
Section: Resultsmentioning
confidence: 99%